The Development of a Biotechnology Product Innovation Strategy for The Medium-Scale Seaweed Industry Company in Indonesia on The Company’s Business Growth - Buana, Archie Sultan Eka; Ratnaningtyas, Sudrajati (International Journal Of Management And Economics Invention, 2022)
Biotechnology is a developmental process of product innovation that can provide many benefits to the environment and consumers. One resource that has great potential is derived from the sea, namely seaweed. Utilization of Seaweed product innovation using a biotechnology approach can be a new prospect for various industries in the future. This study aims to see what strategies can be carried out for business actors in this industry to increase their business growth. The method used in this study was to survey respondents using convenience sampling and analyzed descriptively. The data obtained in this study is regarding consumer demographics, awareness from consumers and also perceptions regarding the importance and how the innovation strategy should be carried out for seaweed biotechnology products. The results obtained show that the level of knowledge of respondents regarding the innovation of seaweed biotechnology products is still low, but there is confidence from respondents regarding the potential benefits of this product innovation in the future. It can be concluded in this research that product innovation must continue to be improved by being oriented towards consumer needs and must also be accompanied by a good marketing strategy, especially in increasing digitalization which can make it easier to reach target buyers.